Correlation of Legal Change Theory to Collection of Cash Waqf Linked Retail Sukuk in Sharia Bank - Tuti Aditama (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Indonesian waqf has enormous potential for national economic development. However, the use of waqf land is still limited to the construction of worship facilities. In October 2020 the government issued Cash Waqf Linked Sukuk Retail (CWLS Retail) to finance social programs and economic empowerment of the ummah. The Sukuk Waqf scheme was prepared by the waqf authority with the Government in order to support the development of Islamic finance and social investment in Indonesia. PT Bank Syariah Indonesia, Tbk acts as a Sharia Financial Institution Recipient of Cash Waqf (LKSPWU), in collecting Cash Waqf Linked Sukuk PT Bank Syariah Indonesia, Tbk in cooperation with Nadzir with certain terms and conditions. Retail CWLS is implemented through Islamic financial institutions through two mechanisms, namely offline and digital. The practice of collecting digital waqf that is not accommodated in the Waqf Law, so that legal changes are needed to compensate for market changes and social encouragement from the community on an investment instrument that does not only consider returns for individuals but the launch of CWLS Retail should have a bigger goal, namely maintaining sharia maqasid.